Os sobreviventes: O direito à comunicação na produção do programa “Conexões Periféricas” - Torres, Francisco George Costa (2020)
In this research, we sought to understand whether and how the right to communication was exercised in the 4th season of the program Conexões Periféricas. In this process, aspects were considered: agenda meetings, recording meetings and interactions in Whatsapp groups. To support the presented reflections, we start from the central idea of the communication rights, taking as reference authors like Barros (2014), Gomes (2007), Guareschi (2013), Lima (2011), Matellart (2009), and Peruzzo (2007) in dialogue with youth issues, as presented by Abramo (1997), Barbalho (2013, 2007), Dayrell (2005), Pais (1990) and Sposito (2000). Normative documents, such as the Estatuto da Juventude (Lei 12.852), also guided the investigation, which guides public policies applied by Rede Cuca, in particular. The research methodological proposal is ethnography, using participant observation, in the perspective of Angrosino (2012), Clifford (2008), Geertz (2008, 2009), Guber (2001), Magnani (1984), Oliveira (2006), Peruzzo (2012), Ramalho (2013) and Silva (2009). The field trip took place from September 2018 to April 2019, and implied an active presence in the entire training process, helping to build the scripts, accompanying the recordings and assisting in the entire program planning. It was observed that the right to communication was, at various times, neglected in the formation and production of the program, by restricting the autonomy of the participants, the numerous censures and lack of transparency in the transfer of information. These factors were crucial in the development of the entire process, including slowing down the production pace of Conexões and acting to discourage the participants throughout the project. Keywords: Communication rights. Youth. Cuca.